Role of IL-17-producing lymphocytes in severity of multiple sclerosis upon natalizumab treatment. (April 2017) - Bühler, Ulrike; Fleischer, Vinzenz; Luessi, Felix; Rezk, Ayman; Belikan, Patrick; Graetz, Christiane; Gollan, René; Wolf, Christina; Lutz, Jens; Bar-Or, Amit; Siffrin, Volker; Zipp, Frauke
Objective: Natalizumab is known to prevent T-helper cells entering the central nervous system (CNS). We hypothesize that more pathogenic T-helper cells are present outside the CNS and a possible relationship to disease severity. Methods: Characterization and enrichment of human CD4+IL-17+ cells were performed ex vivo using peripheral blood mononuclear cells from natalizumab-treated relapsing-remitting multiple sclerosis (RRMS) patients ( n  = 33), untreated RRMS patients ( n  = 13), and healthy controls ( n  = 33). Magnetic resonance imaging (MRI) scans were performed routinely for patients. Results: Lymphocytes were elevated in peripheral blood of natalizumab-treated patients compared to untreated patients and healthy controls. Whereas group comparison for CD4+IL-17+ numbers also differed, CD4+IFN-γ+ and CD4+IL-22+ counts were not increased. CD4+IL-17+ cells not only expressed but also secreted IL-17. In natalizumab-treated patients, IL-17+ cell frequency was found to correlate with T1-hypointense lesions, but was not an indicator for rebound activity after treatment discontinuation, except in one patient who experienced a fulminant rebound, and interestingly, in whom the highest IL-17+ cell levels were observed. Conclusion: Increased lymphocytes and CD4+IL-17+ cells in the blood of RRMS patients receiving natalizumab corroborate the drug's mechanism of action, that is, blocking transmigration to CNS. Correlation between IL-17-expressing lymphocytes and T1-hypointense lesions underlines the important role of these cells in the disease pathology.